ANALISIS STRATEGI PEMASARAN PRODUK DIGITALCRM DI PT INFOMEDIA NUSANTARA - Erlina Aduski, (2020)
This thesis explain about marketing strategy analysis at PT Infomedia Nusantara to increase sales of Digital CRM product. The purpose of this research is to find out existing marketing strategy of Digital CRM products and reformulate the strategy based on the alternative strategies which proposed by researcher. This research applied the qualitative approach with descriptive type of research and using PEST analysis, Industry Environment 5 Forces Porter Analysis, 7S Mckinsey, SWOT, STP and 7P Marketing Mix.Based on the analysis of external and internal factors, we get several alternative strategy such as : Segments: Domestic Market and Global Market, Targeting: 6 business segments, like Government / Public Sector, Telecommunication, Finance Banking & Insurance (FBSI), Food & Beverage, Transportation, FMCG (Fast Moving Customer Goods) and Manufacture. Positioning: Providing analytics enablers as a competitive advantage. Product: 1) Focus on offering CRM as Managed Service, 2) Focus on offering Integrated Omnichannel products 3) Increasing maturity of application or platform 4) Providing analytics enablers as a competitive advantage, Price: 1) Implementing a flexible business scheme and conducting Cost Leadership, Place: 1) Maximizing Telkom's Customer Facing Unit (CFUE) for marketing channels, 2) Global penetration, People: 1) Building capabilities and competencies through training, certification and sharing session, 2) Redefine Job Roles and making project delivery policies 3) Developing roadmap for operational talent Promotion : 1) Creating Brand Awareness, and Channel Awareness 2) Focus on internal promotion at TelkomGroup PT Infomedia Nusantara can run optimally its competitiveness by determining these strategic priority in the implementation